Enhanced phosphorylation of sphingosine and ceramide sustains the exuberant proliferation of endothelial progenitors in Kaposi sarcoma. Issue 3 (15th December 2017) - Abdel Hadi, Loubna; Calcaterra, Francesca; Brambilla, Lucia; Carenza, Claudia; Marfia, Giovanni; Della Bella, Silvia; Riboni, Laura
Abstract: Endothelial colony-forming cells (ECFCs), a unique endothelial stem cell population, are highly increased in the blood of Kaposi sarcoma (KS) patients. KS-derived ECFCs (KS-ECFCs) are also endowed with increased proliferative and vasculogenic potential, thus suggesting that they may be precursors of KS spindle cells. However, the mechanisms underlying the increased proliferative activity of KS-ECFCs remain poorly understood. Sphingosine-1-phosphate (S1P) and ceramide-1-phosphate (C1P) are metabolically interconnected sphingoid mediators crucial to cell proliferation. Here, we investigated the metabolism, release, and proliferative effects of S1P and C1P in KS-ECFCs compared with control ECFCs (Ct-ECFCs). Metabolic studies by cell labeling, chromatographic analyses, and digital autoradiography revealed that S1P and C1P biosynthesis and S1P secretion are all efficient processes in KS-ECFCs, more efficient in KS-ECFCs than Ct-ECFCs. Quantitative PCR analyses demonstrated a significantly higher ceramide kinase and sphingosine kinase-2 expression in KS-ECFCs. Notably, also the expression of S1P1 and S1P3 receptors was augmented in KS-ECFCs. Accordingly, treatment with exogenous C1P or S1P induced a significant, concentration-dependent stimulation of KS-ECFC proliferation, but was almost completely ineffective in Ct-ECFCs. Hence, we identified C1P and S1P as autocrine/paracrine proliferative signals in KS-ECFCs. A better understanding of the mechanisms that enhance S1P/C1P formation in KS-ECFCs may yield effective therapeutic modalities.